Exergoeconomic analysis as support in decision-making for the design and operation of multiple chiller systems in air conditioning applications. (15th September 2020) - Catrini, P.; Piacentino, A.; Cardona, F.; Ciulla, G.
Highlights: A novel use of Exergoeconomics to optimize multiple-chillers systems is proposed. The method represents support for decision-making at the design and operational stage. Design options regarding chillers' size and parallel or series configurations are compared. Operational strategies based on "symmetric" and "sequential" loading of chillers are examined. The lowest unit exergoeconomic cost identifies the best design or operation strategy. Abstract: Multiple-chillers systems represent viable solutions for medium/large-scale air conditioning applications characterized by variable cooling demand. The energy efficiency of such systems is influenced by the number of chillers, the combination of cooling capacities, and the load-sharing among the units. Large efforts have been devoted to developing efficient operation strategies for these systems, but rules of thumb are usually adopted for selecting cooling capacities thus leaving room for energy and economic savings. In this paper, exergoeconomic analysis is proposed as a promising method to identify near-optimal design and operation strategies, due to the capability of exergoeconomic indicators to account simultaneously for capital and operating costs. The potential of the method is illustrated for a hydronic system supplying an air-handling unit installed in an office building. Design alternatives are compared, with chillers of equal or different capacities operated in a parallel or series configuration, and the cost-effectiveness of different load sharing strategies is also investigated. A thermoeconomic model for multiple-chillers systems is formulated, considering the actual performance of chillers under full- and part-load conditions derived by a plant simulator. Results show that the exergoeconomic cost of chilled water reduced by about 7% and 30% when passing from evenly to unevenly sized systems in both series and parallel configurations. It is also found that the symmetric load sharing strategy leads to a 14–18% reduction in the cost of chiller water compared to the sequential one. The study confirms that this method may represent systematic and thermodynamically-sound support for engineers in this field.